Ir(III)-catalyzed carbenoid functionalization of benzamides: synthesis of N-methoxyisoquinolinediones and N-methoxyisoquinolinones - Phatake, Ravindra S.; Patel, Pitambar; Ramana, Chepuri V. (Organic Letters, 2016)
A mild and efficient Ir(III)-catalyzed C-H carbenoid functionalization strategy has been developed to access. N-methoxyisoquinolinediones and N-methoxyisoquinolinones. The reaction proceeds efficiently in high yield at room temperature over a broad range of substrates without requirement of any additional oxidants or a base.